Row upon row : sea grass baskets of the South Carolina lowcountry - Rosengarten, Dale, 1948- (University of South Carolina Press, 2022)
"Coiled grass baskets are icons of Gullah culture. From their roots in Africa through their evolution on Lowcountry rice plantations to their modern recognition as art, they carry centuries of African American and South Carolina history. Fanner baskets were essential for rice processing, and baskets were sold between plantations as early as 1774; after emancipation, Black families used coiled baskets in their homes and to transport vegetables to market; in the early twentieth century, coinciding with the Arts and Crafts movement, students at the Penn School on St. Helena Island, made baskets to sell in Charleston and as far off as Boston. By the end of the last century, the basketmaking tradition was centered in Mt. Pleasant and focused on art baskets produced for sale. The first full-scale description of the history of this folk art, Row upon Row remains a classic in the field. Today the artform continues to evolve in response to the changing consumer market, availability of materials, economic opportunities, and most recently, increased traffic near the traditional highway basket stands. This new edition of the book features an additional essay by the author, which brings the narrative into the twenty-first century, featuring artists including MacArthur Fellowship receipient Mary Jackson and Antwon Ford and describing current challenges to the survival of the time-honored tradition. As globalization transforms our world, the sweetgrass basket in all its iterations retains its power as a local symbol of individual identity and cultural distinction. Making baskets is a meditative act, a form of labor and a collective process that strengthens families and links generations. While each sewer pursues her or his art out of personal necessity, all feel a shared sense of guardianship of the region, and a debt to a tradition sanctioned by their ancestors"--